Ecology of Fishes in Tasek Bera, Pahang, Malaysia / Fatimah Abdullah - Abdullah, Fatimah (2012)
The ecology of fishes was investigated in Tasek Bera (Lake Bera), a peat swamp ecosystem with three major habitats: (i) swamp forest dominated by Eugenia, (ii) Reed (Lepironia) and clumps of Pandanus stands and (iii) open waters fringed by submerged Utricularia. Limnological information and fish fauna of the lake was determined and the association of both data was done using canonical correspondence analysis (CCA).Mean values of water quality parameters for the entire study period (April 2004 to December 2005) were as follows: water temperature = 29.540 C ± 1.15; total suspended solids (TSS) = 19.38 mg/L ± 28.32; total dissolved solids (TDS) = 31.64 mg/L ± 4.87; turbidity = 8.03 NTU ± 4.61; conductivity = 44.85 μS/cm ± 5.65; dissolved oxygen(DO) = 3.66 mg/L ± 1.28; pH = 5.77 ± 0.76; hydrogen sulphide = 1.11 μg/L ± 3.16; nitrite = 4.63 μg/L ± 9.81; ammonium = 67.80 μg/L ± 66.71; ammonia = 0.38 μg/L ± 0.46. There were statistically significant differences in values of water quality parameters across sampling stations and depths. Only TSS, TDS, conductivity and DO were not significantly different during three sampling times (0600, 1400 and 2200 hours). Temperature and conductivity were higher compared to 30 years ago. Whereas, pH, nitrite and ammonium were lower than 30 years ago. The ichthyofaunal composition of Tasek Bera based on museum collections and present collections of fish revealed that 95 species representing 22 families were known to inhabit the wetlands. Four species were considered to be locally extinct, while 66 species were considered to be extremely rare or rare. The rare and much sought after Asian bonytongue, Scleropages formosus was still present as it was collected during the sampling effort. Botia hymenophysa which was recorded as a dominant species in the past is now difficult to find. Fourteen species were recorded for the first time in the area.They include: Amblyrhynchichthys truncatus, Boraras maculates, Chela laubuca,Epalzeorhynchos kalopterus, Macrochirichthys macrochirus and Osteochilus microcephalus of the family Cyprinidae; Acanthopsoides molobrion,Lepidocephalichthys furcatus and Pangio malayana of the family Cobitidae; Channa gachua of the family Channidae; Kryptopterus moorei of the family Siluridae; Akysis alfredi of the family Akysidae; Macrognathus maculatus of the family Mastacembelidae and Betta waseri of the family Osphronemidae. The most common species were Labiobarbus festivus and Cyclocheilichtys apogon both from the family Cyprinidae. Based on past and current studies, a total of 144 species has been reported from Tasek Bera includes several doubtful occurrences and incomplete identification.The vertical distribution of fishes investigated at 11 study sites by using vertical gill nets revealed that Lubuk Salleh has the highest diversity and biomass compared to other study sites. Cyprinids Labiobarbus festivus (ikan kawan) and Hampala macrolepidota (ikan sebarau) were found at all sites. Barbonymus schwanenfeldii,Cyclocheilichthys apogon, Hampala macrolepidota, Labiobarbus festivus and Kryptopterus apogon occurred at almost all depth layers. Depth 0 to 1 m had the highest diversity followed by depth 2 to 3 m and depth 1 to 2 m. Catch per unit effort (CPUE)and abundance of species were much higher during evening and night compared to the early part of the day. A canonical correspondence analysis (CCA) showed that depth,dissolved oxygen and pH were the most important factors influencing the vertical distribution of the fish species.The most successful species in Tasek Bera, Labiobarbus festivus has inferior mouth with upper and lower jaws protrusive and toothless. Both jaws have truncate unculi with polygonal borders. The gill has short gill rakers with the space between adjacent rakers not very closely packed. Relative Important Index (%) of L. festivus diet show that algae represented 55.7%, followed by detritus and plant (26.8%) and zooplankton (17.5%). Bacillariophyta is the most important component in term of,number, whereas detritus and plant contributed more than 50% in terms of volume.From the recent study L. festivus can be generalised as an omnivore.